A new species of Pomatoschistus (Teleostei: Gobiidae) from Southern Anatolia. Issue 4 (2nd October 2017) - Engin, Semih; İnnal, Deniz
Abstract : Pomatoschistus anatoliae sp. n. is described from estuary of Göksu River on the Mediterranean coast of the Anatolia. It is distinguished from its congeners by the suborbital papilla pattern, meristic, and ecological features. DNA barcoding based on COI sequences revealed that there is a high nucleotide sequence divergence to the nearest neighbour. Kimura's two parameter distances between P. anatoliae sp. n. and other species of Pomatoschistus and Knipowitchia have found to be at least 5.1%. http://www.zoobank.org/urn:lsid:zoobank.org:pub:4592CF50-07B5-4C25-892F-5D009057675B